A Preliminary Model of Learning Analytics to Explore Data Visualization on Educators Satisfaction and Academic Performance in Higher Education - Shahril Khuzairi N.M.; Che Cob Z. (Springer Science and Business Media Deutschland GmbH, 2023)
Computer aided instruction; Decision making; Digital storage; E-learning; Education computing; Learning systems; Online systems; Students; Teaching; Visualization; Academic performance; Decisions makings; High educations; IS success; IS success model; Learning analytic; Models of learning; Online learning; Preliminary model; Technology acceptance model; Data visualization